PROBABILISTIC MODEL FOR LONGITUDINAL ORIENTATION PROCESS OF CEREAL STRAW STALKS - Yury I. Yermolyev; Andrey V. Butovchenko; Sergey V. Belov; Roman E. Fomenko (Advanced Engineering Research, 2012)
A general approach to the development of the stochastic mathematical model of the longitudinal orientation process of the long strawy fractions on the special orienting device is given.